The Effectiveness of Preceptorship Programs in Improving Clinical Competence among Novice Nurses: A Systematic Review - Maria Wea; Rr. Tutik Sri Hariyati; Hanny Handiyani; Andi Amalia Wildani (Faculty of Nursing, Universitas Pelita Harapan, 2025)
The transition period for new nurses is often characterized by adaptation-related stress, limited clinical experience, and insufficient supervision. Preceptorship offers structured support that helps accelerate competency development and enhance clinical readiness for practice. To evaluate the effectiveness of preceptorship programs in improving clinical competence in novice nurses. A systematic search was conducted in PubMed, ScienceDirect, ProQuest, and Google Scholar from August 2019 to April 2025, following the PRISMA 2020 guidelines and registered PROSPERO protocol. This review included quantitative studies involving new nurses who received structured preceptorship interventions with clinical competency as the primary outcome. Eligible study designs comprised randomized controlled trials, quasi-experimental studies, uncontrolled pre–post trials, and cross-sectional surveys. Qualitative studies, student-based programs, and orientations without preceptors were excluded. Two reviewers independently conducted study selection, data extraction, and methodological quality appraisal using the JBI critical appraisal tools. The findings were synthesized narratively. Ten studies consistently demonstrated that preceptorship programs improved clinical competence, confidence, and readiness for practice. Eight studies reported significant improvements (p < 0.05). Effective programs included individualized supervision, structured feedback, and standardized competency assessments. Critical success factors included preceptor readiness, continuity of preceptorship, organizational support, and reduced transition shock. The findings indicate that well-structured preceptorship programs can enhance the clinical competence and self-confidence of novice nurses. Healthcare institutions are encouraged to adopt standardized preceptorship frameworks, allocate adequate resources, and provide ongoing training and support for preceptors to strengthen practice readiness, improve quality of care, and promote nurse retention.